Tools and Algorithms for the Construction and Analysis of Systems 22nd International Conference, TACAS 2016, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2016, Eindhoven, The Netherlands, April 2-8, 2016, Proceedings - Chechik, Marsha; Raskin, Jean-François (Theoretical Computer Science and General Issues,, 2016)
This book constitutes the proceedings of the 22nd International Conference on Tools and Algorithms for the Construction and Analysis of Systems, TACAS 2016, which took place in Eindhoven, The Netherlands, in April 2016, held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2016. The 44 full papers presented in this volume were carefully reviewed and selected from 175 submissions. They were organized in topical sections named: abstraction and verification; probabilistic and stochastic systems; synthesis; tool papers; concurrency; tool demos; languages and automata; security; optimization; and competition on software verification - SV-COMP.